10 + 2 x 2 + 6 x 2 + 4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: 2*2*2*2*2*2=2^6
2: x*x*x*x=x^4
3: =7^4*6^4=42^4
4: =5^2*3^2*4^2=60^2
5: =2*3^2*5^5
6: =10^3*10^3=10^6
1) 62 . x = 36
=> x = 36 / 36 = 1
2) 9x - 42 = 11
9x - 16 = 11
9x = 11 + 16 =27
=> x = 27/9=3
3) 10 + 2x = 42
2x = 16 - 10 =6
=> x = 3
4) 231 - ( x - 6 ) =103
( x - 6 ) = 231-103=128
=> x = 128+6=134
5) 10 + 3x = 45 / 42
3x = 43-10=64-10=54
x = 18
6)25 + 52x = 82 + 62
25 + 25x = 100
25x = 100-25=75
=> x = 75/25=3
*Chúc bạn học tốt*
1) 62.x=36 2) 9.x-42=11 3)10+2.x=42 4)231-(x-6)=103 5)10+3x=45:42 6)25+52.x=82+62
36.x=36 9.x-16=11 10+2.x=16 x-6 = 231-103 10+3x=43 25+25.x =64+36
x=36:36 9.x =11+16 2.x =16-10 x-6 =128 10+3x=64 25+25.x =100
x=1 9.x =27 2.x =6 x =128+6 3x=64-10 25.x =100-25
x =27:9 x =6:2 x =134 3x=54 25.x =75
x =3 x =3 x=54:3 x =75:25
x=18 x =3
\(x^2=1\Rightarrow\left[{}\begin{matrix}x=-1\\x=1\end{matrix}\right.\)
\(x^2=3\Rightarrow\left[{}\begin{matrix}x=-\sqrt{3}\\x=\sqrt{3}\end{matrix}\right.\)
\(x^2=5\Rightarrow\left[{}\begin{matrix}x=-\sqrt{5}\\x=\sqrt{5}\end{matrix}\right.\Rightarrow x=-\sqrt{5}\left(vì.x< 0\right)\)
\(x^2=7\Rightarrow\left[{}\begin{matrix}x=-\sqrt{7}\\x=\sqrt{7}\end{matrix}\right.\Rightarrow x=-\sqrt{7}\left(vì.x< 0\right)\)
\(x^2=9\Rightarrow\left[{}\begin{matrix}x=-3\\x=3\end{matrix}\right.\)
\(\left(x-2\right)^2=2\Rightarrow\left[{}\begin{matrix}x-2=-\sqrt{2}\\x-2=\sqrt{2}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=2-\sqrt{2}\\x=2+\sqrt{2}\end{matrix}\right.\)
\(\left(x-4\right)^2=4\Rightarrow\left[{}\begin{matrix}x-2=-2\\x-2=2\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=4\end{matrix}\right.\)
\(\left(x-6\right)^2=6\Rightarrow\left[{}\begin{matrix}x-6=-\sqrt{6}\\x-6=\sqrt{6}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=6-\sqrt{6}\\x=6+\sqrt{6}\end{matrix}\right.\)
\(\left(x-8\right)^2=8\Rightarrow\left[{}\begin{matrix}x-8=-2\sqrt{2}\\x-8=2\sqrt{2}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=8-2\sqrt{2}\\x=2+2\sqrt{2}\end{matrix}\right.\)
\(\left(x-10\right)^2=10\Rightarrow\left[{}\begin{matrix}x-10=-\sqrt{10}\\x-10=\sqrt{10}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=10-\sqrt{10}\\x=10+\sqrt{10}\end{matrix}\right.\)
\(\left(x-\sqrt{3}\right)^2=3\Rightarrow\left[{}\begin{matrix}x-\sqrt{3}=-\sqrt{3}\\x-\sqrt{3}=\sqrt{3}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=2\sqrt{3}\end{matrix}\right.\)
\(\left(x-\sqrt{5}\right)^2=5\Rightarrow\left[{}\begin{matrix}x-\sqrt{5}=-\sqrt{5}\\x-\sqrt{5}=\sqrt{5}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=2\sqrt{5}\end{matrix}\right.\)
Tham khảo:
b)
c)
7 x 4 + 3 x 4 = (7 + 3) x 4
= 10 x 4
= 40
12 x 2 + 4 x 2 + 4 x 2 = (12 + 4 + 4) x 2
= 20 x 2
= 40
6) ĐKXĐ: \(x\le-6\)
\(\sqrt{\left(x+6\right)^2}=-x-6\Leftrightarrow\left|x+6\right|=-x-6\)
\(\Leftrightarrow x+6=x+6\left(đúng\forall x\right)\)
Vậy \(x\le-6\)
7) ĐKXĐ: \(x\ge\dfrac{2}{3}\)
\(pt\Leftrightarrow\sqrt{\left(3x-2\right)^2}=3x-2\Leftrightarrow\left|3x-2\right|=3x-2\)
\(\Leftrightarrow3x-2=3x-2\left(đúng\forall x\right)\)
Vậy \(x\ge\dfrac{2}{3}\)
8) ĐKXĐ: \(x\ge5\)
\(pt\Leftrightarrow\sqrt{\left(4-3x\right)^2}=2x-10\)\(\Leftrightarrow\left|4-3x\right|=2x-10\)
\(\Leftrightarrow4-3x=10-2x\Leftrightarrow x=-6\left(ktm\right)\Leftrightarrow S=\varnothing\)
9) ĐKXĐ: \(x\ge\dfrac{3}{2}\)
\(pt\Leftrightarrow\sqrt{\left(x-3\right)^2}=2x-3\Leftrightarrow\left|x-3\right|=2x-3\)
\(\Leftrightarrow\left[{}\begin{matrix}x-3=2x-3\left(x\ge3\right)\\x-3=3-2x\left(\dfrac{3}{2}\le x< 3\right)\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=0\left(ktm\right)\\x=2\left(tm\right)\end{matrix}\right.\)
a)\(\left(x-2\right)^2-\left(x-3\right)\left(x+3\right)=6.\)
\(\Leftrightarrow x^2-4x+4-x^2+9-6=0\)
\(\Leftrightarrow-4x+7=0\)
\(\Leftrightarrow4x=7\Leftrightarrow x=1,75\)
\(b,4\left(x-3\right)^2-\left(2x-1\right)\left(2x+1\right)=10.\)
\(\Leftrightarrow4\left(x^2-6x+9\right)-4x^2+1-10=0\)
\(\Leftrightarrow-24x+27=0\)
\(\Leftrightarrow24x=27\Leftrightarrow x=1,125\)
a: \(=\dfrac{6}{x+1}+\dfrac{4}{x-1}-\dfrac{10}{\left(x-1\right)\left(x+1\right)}\)
\(=\dfrac{6x-6+4x+4-10}{\left(x-1\right)\left(x+1\right)}=\dfrac{10x-12}{\left(x-1\right)\left(x+1\right)}\)
b: \(=\dfrac{1}{x}-\dfrac{1}{x+2}+\dfrac{1}{x+2}-\dfrac{1}{x+4}+\dfrac{1}{x+4}-\dfrac{1}{x+6}+\dfrac{6}{x}=\dfrac{1}{x}+\dfrac{6}{x}=\dfrac{7}{x}\)
1/ 10(X-7)-8(X+5)=6(-5)+24
10x - 70 - 8x - 40 = -30 +24
2x - 110 = -6
2x = 104
x=52
2/ 8(X-|-7|)-6(X-2)=|-8|.6-50
8(x - 7) - 6(x-2) = 8.6 - 50
8x - 56 - 6x +12 =48 -50
2x - 44 = -2
2x = 42
x=21
3/ 2(4X-8)-7(3+X)=|-4|(3-2)
8x-16 - 21 - 7x = 4.1
x-37=4
x=41
4/ 12(X-4)=6(x-2)-16(X+3)=7|-4|
12x - 48 = 6x - 12 - 16x -48 =7.4
12x - 48 = 28
12x=76
x=19/3
5/ 4(X-5)-7(5-X)+10(5-X)=-3
4x - 20 -35 +7x + 50 -10x = -3
x - 5 = -3
x = -2
Chúc bạn học tốt!
10 + 2 x 2 + 6 x 2 + 4
= 10 + 4 + 12 + 4
= 14 + 16
= 30
10+4+12+4=30